Does all-day and long-term exposure to radiofrequency radiation emitted from Wi-Fi affect hearing?. Issue 6 (2nd November 2017) - Yorgancilar, Ediz; Dasdag, Suleyman; Akdag, Mehmet Zülküf; Akkus, Zeki; Akdag, Mehmet; Topcu, Ismail
ABSTRACT: We investigated the long-term effects of radiofrequency radiation (RFR) emitted from Wi-Fi systems on hearing. Sixteen Wistar albino rats were divided equally into two groups: sham control and exposure groups. The rats in the experimental group were exposed to 2.4 GHz RFR emitted from a Wi-Fi generator for 24 h/day for one year. The same procedure was applied to the rats in the sham group, except that the Wi-Fi generator was turned off. All groups were kept in Faraday cages during the 12 months to eliminate external electromagnetic fields. The distance between the Wi-Fi generator antenna and the exposure cages was 50 cm. Pre-exposure distortion product otoacoustic emissions (DPOAE) of all rats were measured at the beginning, 6th and 12th months of the study. The DPOAE values of the sham, baseline and exposure groups were compared statistically. For the 6000 Hz hearing frequency, the DPOAE values in the exposure group were lower than those in the sham group ( p < 0.05). Similarly, the 6000 Hz hearing frequency values obtained at the end of the 12th month were also lower than the baseline and 6-month values in the exposure group ( p < 0.05). In contrast, the DPOAE values at the 6th and 12th months of exposure for the 2000 Hz hearing frequency were higher than the baseline value ( p < 0.05). These results indicated that 12 months of RFR (24 h/day) at 50 cm from a 2.4 GHz Wi-Fi source can affect hearing. However, further studies are necessary.